Holger Gzella, A Cultural History of Aramaic: From the Beginnings to the Advent of Islam (Handbook of Oriental Studies / Handbuch der Orientalistik. Section 1. The Near and Middle East 111; Leiden-Boston: Brill 2015) - Lipiński, Edward (The Biblical Annals, 2016)
Book review: Holger Gzella, A Cultural History of Aramaic: From the Beginnings to the Advent of Islam (Handbook of Oriental Studies / Handbuch der Orientalistik. Section 1. The Near and Middle East 111; Leiden - Boston: Brill 2015). Pp. XIV + 451. €162,00. ISBN 978-90-04-28509-5, ISSN 0169-9423.